In Silico Study of Pulutan (Urena lobata) Leaf Extract as Anti Inflammation and their ADME Prediction - Doti Wahyuningsih; Yudi Purnomo; Andri Tilaqza (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2022)
Inflammation is the basic for the pathogenesis of several diseases both of degenerative and non-degenerative disease. Urena lobata is a medicinal plant that can be found in Indonesia and has been used traditionally to cure influenza, inflammation and fever. However, there have been few reports about their anti-inflammatory activity and their mechanism action are still unclear. The aim of study to evaluate the anti-inflammatory activities of active substances from U.lobata leaf and their pharmacokinetic property through in silico study. lobata leaf was extracted by digeration methods using ethanol solvent. Therefore, the active substances in the extract was analyzed by Liquid Chromatography-Mass Spectra (LC-MS). Pharmacokinetic property and physicochemical of active compounds were evaluated using pkCSM online tool. Anti-inflammatory activity of U. lobata active compound on phospholipase-A2 (PLA-2), cyclooxygenase-2 (COX-2) and lipoxygenase-5 (LOX-5) were evaluated by in silico study. Ethanolic extract of U. lobata contained five active compound, there are stigmasterol, ?-sitosterol mangiferin, gossypetin and chrysoeriol. Molecular docking study indicated stigmasterol and ?-sitosterol of U. lobata have a strong activity as anti-inflammatory based on the estimation of inhibition constant (Ki) value against PLA2 and COX-2. Meanwhile, mangiferin and gossypetin have a stronger anti-inflammatory effect on LOX-5 among others compound. U. lobata has anti-inflammatory activity through inhibition on COX-2 greater than on PLA2 and LOX-5.